South East Europe Regular Economic Report, No. 8, Fall 2015 : Growth Recovers, Risks Heighten - World Bank Group (World Bank, Washington, DC, 2016)
Economic activity in the six South East European countries (SEE6) is picking up speed, and growth in the region is expected to average 1.8 percent for 2015. The highest growth rates projected are 3.4 percent for Montenegro and 3.2 percent for FYR Macedonia; the lowest is Serbia’s 0.5 percent. Although they trail the rest of the SEE6 region, Serbia and Bosnia and Herzegovina, which were hit heavily by floods in mid-2014, are recovering faster than expected. As 2015 progresses, a recovery in domestic demand is stimulating economic growth throughout the region. Private investment has become the main driver of growth. Developments in the global economy have also helped, especially lower oil prices and a pick-up in demand in the European Union (EU), a major market for the region.